2022
DOI: 10.1002/jimd.12570
|View full text |Cite
|
Sign up to set email alerts
|

Relief of CoA sequestration and restoration of mitochondrial function in a mouse model of propionic acidemia

Abstract: Propionic acidemia (PA, OMIM 606054) is a devastating inborn error of metabolism arising from mutations that reduce the activity of the mitochondrial enzyme propionyl-CoA carboxylase (PCC). The defects in PCC reduce the concentrations of nonesterified coenzyme A (CoASH), thus compromising mitochondrial function and disrupting intermediary metabolism. Here, we use a hypomorphic PA mouse model to test the effectiveness of BBP-671 in correcting the metabolic imbalances in PA. BBP-671 is a high-affinity allosteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 103 publications
(252 reference statements)
0
12
0
Order By: Relevance
“…A first-in-human trial to assess the safety and tolerability of an improved pantazine (BP-671) in healthy volunteers has recently begun (NCT04836494). The molecule was also proposed as a therapeutic option for patients with Propionic Acidemia and Methylmalonic Acidemia [ 132 ].…”
Section: Proposed Therapeutic Optionsmentioning
confidence: 99%
“…A first-in-human trial to assess the safety and tolerability of an improved pantazine (BP-671) in healthy volunteers has recently begun (NCT04836494). The molecule was also proposed as a therapeutic option for patients with Propionic Acidemia and Methylmalonic Acidemia [ 132 ].…”
Section: Proposed Therapeutic Optionsmentioning
confidence: 99%
“…Earlier studies have demonstrated the mitochondrial protective function of pantothenic acid (Tahiliani & Beinlich 1991, Williams et al 2013, Sm et al 2018, Subramanian et al 2021, Subramanian et al 2023. Pantothenic acid is a major precursor for CoA synthesis (Tahiliani & Beinlich 1991, Williams et al 2013, Sm et al 2018, Subramanian et al 2021, Subramanian et al 2023.…”
Section: Figurementioning
confidence: 99%
“…Earlier studies have demonstrated the mitochondrial protective function of pantothenic acid (Tahiliani & Beinlich 1991, Williams et al 2013, Sm et al 2018, Subramanian et al 2021, Subramanian et al 2023. Pantothenic acid is a major precursor for CoA synthesis (Tahiliani & Beinlich 1991, Williams et al 2013, Sm et al 2018, Subramanian et al 2021, Subramanian et al 2023. Pantothenic acid-mediated CoA biosynthesis is required for the effective metabolism of all substrates by converting them to Acetyl CoA which is the preferred form for https://doi.org/10.1530/REM-23-0005…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Pantazines induce a conformational change in homodimeric PanK, which obscures the CoA binding pocket and prevents CoA inhibition. The effects of pantazines are concentration-dependent [ 100 ]. At low concentrations, the majority of PanK protomers are not bound to pantazines, and thus PanK dimerization typically occurs between one bound protomer and one unbound protomer.…”
Section: Development Of Drugs Targeting the Coa Biosynthesis Pathwaymentioning
confidence: 99%